2020
DOI: 10.31219/osf.io/r8dcz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OMG GMO! Parent-Child Conversations About Genetically Modified Foods

Abstract: Studies indicate that Genetically Modified Organisms, or GMOs, are safe to consume, but many adults remain skeptical. What kind of input are children receiving about GMOs? And how does that input shape their understanding of what GMOs are? We investigated this question in the context of parent-child conversations about food product decisions. Seventy parent-child dyads were shown a series of food product pairings and asked to discuss their preferences. The products differed by whether they were made from GMOs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Children are also exposed to information about genetics outside of formal schooling. Cultural messages around genes are pervasive (Nelkin & Lindee, 2010) and parents sometimes discuss genetic concepts with their children (Shtulman et al, 2020). Therefore, children might know and use words related to genetics before they learn their scientific meanings, and they might sometimes use them incorrectly (Smith & Williams, 2007;Venville et al, 2005).…”
Section: Genetics Knowledgementioning
confidence: 99%
“…Children are also exposed to information about genetics outside of formal schooling. Cultural messages around genes are pervasive (Nelkin & Lindee, 2010) and parents sometimes discuss genetic concepts with their children (Shtulman et al, 2020). Therefore, children might know and use words related to genetics before they learn their scientific meanings, and they might sometimes use them incorrectly (Smith & Williams, 2007;Venville et al, 2005).…”
Section: Genetics Knowledgementioning
confidence: 99%
“…It would be interesting to explore the strength of these preferences with more subtle manipulations. Finally, examining parent-child dyadic interactions and the role of parental attitudes in shaping children's naturalness preferences would be a fruitful area for future investigation (see Shtulman et al, 2020) and may offer some insight into the (possible) role of social learning. Although the current data do not directly inform whether social learning is the mechanism through which children come to prefer natural things, they do suggest that, if it is the mechanism, this is well established by 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study has examined the role of the parent-child relationship in in the domain of food naturalness. Shtulman et al (2020) found that children whose parents had better knowledge of the definitions of GM, organic, and gluten-free foods themselves tended to have better knowledge of these terms. However, while they found that adults tended to prefer organic and dislike GM foods, they did not explicitly measure children's preferences, nor ask about perceived naturalness.…”
mentioning
confidence: 95%